Ethical Conflicts of The Accounting Profession in Practicing Islamic Work Ethics - Muthohhari, Abdullah Hanif; Haq, Rima Angelia; Sudaryati, Erina (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2024)
The prior study explains that Islamic work ethics have many positive impacts, such as career satisfaction and organizational commitment. By contrast, based on cognitive dissonance theory, we assume that these effects cannot work properly in an environment that does not support workers to implement it, and this will lead to ethical conflicts and dilemmas. In this study, we wanted to find ethical conflict in accounting professionals who felt that their Islamic values at work conflicted with their duties. We examined 50 Muslim accountants in various regions in Indonesia by distributing an online questionnaire to them. Using the data obtained from the questionnaire, we tested the effect by regression. Nevertheless, before that, the testing process will be carried out by passing preliminary test series such as validity, reliability, classical assumption and correlation tests. The research findings state that the practice of Islamic work ethics significantly positively affects the ethical conflict perceived by accountants. It is identified that accountants who practice Islamic work ethics will inevitably feel ethical conflicts themselves due to the circumstances they feel in the workplace. This research can be a reference for Muslim accountants just starting their careers in mitigating and overcoming ethical conflicts in the new world of work. Companies can integrate work patterns with Islamic values and create reporting mechanisms to accommodate Islamic values. The director needs to be a moral compass for their employees.